The Influence of Self-Compassion and Peer Support on Academic Burnout in Grade XII Students of State Vocational School 9 Semarang - Sari, Novita; Rochmawati, Nikmah; Wahib, Abdul (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Academic burnout in grade XII vocational high school students occurs due to academic pressure such as internships, exams, and external projects. Untreated academic burnout can hinder students' ability to achieve optimal learning outcomes. This study examines the influence of self-compassion and peer support on academic burnout in grade XII students of state vocational high school 9 Semarang.A multiple linear regression analysis was conducted on survey data from 200 Grade XII students at State Vocational School 9 Semarang.Data collection used a modified academic burnout scale from Setyaputri, amodified self-compassion scale from Sugianto, and peer support scale Sarafino and Smith's. Results indicate that the simultaneous effect of self-compassion and peer support on academic burnout with a significance value 0.000 and has an influence contribution of 41.4%, and the remaining 58.6% were influenced by other factors or variables not included in this study.Both have a negative influence, meaning the higher the two variables, the lower the academic burnout. This study recommends the need for programs to improve self-compassion and a supportive social environment to improve student welfare.